Fast and Forceful: Modulation of Response Activation Induced by Shifts of Perceived Depth in Virtual 3D Space - Plewan, Thorsten; Rinkenauer, Gerhard (Frontiers in Psychology, 2016)
Reaction time (RT) can strongly be influenced by a number of stimulus properties. For instance, there was converging evidence that perceived size rather than physical (i.e. retinal) size constitutes a major determinant of RT. However, this view has recently been challenged since within a virtual three-dimensional (3D) environment retinal size modulation failed to influence RT. In order to further investigate this issue in the present experiments response force (RF) was recorded as a supplemental measure of response activation in simple reaction tasks. In two separate experiments participants’ task was to react as fast as possible to the occurrence of a target located close to the observer or farther away while the offset between target locations was increased from Experiment 1 to Experiment 2. At the same time perceived target size (by varying the retinal size across depth planes) and target type (sphere vs. soccer ball) were modulated. Both experiments revealed faster and more forceful reactions when targets were presented closer to the observers. Perceived size and target type barely affected RT and RF in Experiment 1 but differentially affected both variables in Experiment 2. Thus, the present findings emphasize the usefulness of RF as a supplement to conventional RT measurement. On a behavioral level the results confirm that (at least) within virtual 3D space perceived object size neither strongly influences RT nor RF. Rather the relative position within egocentric (body-centered) space presumably indicates an object’s behavioral relevance and consequently constitutes an important modulator of visual processing.